Palinología del santoniano tardío al maastrichtiano del piedemonte llanero colombiano. correlación con el paleocinturón tropical (2000)
The palynological analysis of outcrop samples from the E foothills of the Eastern Cordillera, corresponding to the top of the Chipaque Formation, Guadalupe Group and Guaduas Formation, establishes the presence of dinoflagellates, pollen and spores of appreciable biostratigraphic value. The potential of correlation of these elements is compared with data from other parts of the world in the tropical belt, for the interval Late Santonian – Late Maastrichtian.  The Late Santonian is represented in the mudstones of the Chipaque Formation, by the common occurrence of the genus Dinogymnium, specifically by the first appearance of D. digitus and D. Vozzhennikovae, and the last appearance of D. longicornis. Additionally, the last appearance of Xenascus ceratioides is registered in the upper part of the Chipaque Formation. The Early Campanian Arenitas de San Antonio Formation of the Lower Guadalupe Alloformation, is characterized by the first appearance of Trichodinium castanea, Cerodinium granulostriatum and Andalusiella mauthei punctata, as well as the last appearance of Areoligera senonensis, Palaeohystrichophora infusorioides, Dinogymnium westralium, D. undulosum, D. vozzhennicovae and Odontochitina operculata. The association that differentiates palynologically the Late Campanian, is present in the Lodolitas de Aguacaliente Formation of the Middle Guadalupe Alloformation and exhibits the following characteristics: First occurrence of Senegalinium bicavatum, Andalusiella mauthei aegyptiaca, A. gabonenesis, Cerodinium diebellii and Anphigymnium mitratum, and last presence of Trichodinium castanea, A. mauthei punctata, Cerodinium granulostriatum and Alisogymnium euclaensis. The Early Maastrichtian Arenitas de San Luis de Gaceno Formation of the Upper Guadalupe Alloformation is characterized by the last occurrence of Senegalinium bicavatum, Cerodinium diebellii, Cerodinium granulostriatum and Andalusiella mauthei. The upper boundary of the Late Maastrichtian Guaduas Formation corresponds to the unconformity at the base of the (Late Paleocene) Socha Inferior Formation. The palynological association is comparable with the one found in the lower part of the same unit in the locality of Sutatausa. The last occurrence of Andalusiella gabonensis, Dinogymnium acuminatum and Buttinia andreevii defines the Late Maastrichtian. Biostratigraphic studies from other parts of the world have demonstrated the provinciality of Late Cretaceous dinoflagellates. The association that characterizes the Campanian corresponds to the province of the "paleocinturón tropical" and contains species of the genus Andalusiel/a, Trichodinium, Cerodinium and Senegalinium, in several localities of Northem South America and Africa. However, some of these groups display a dispersion that extends to the North Hemisphere, like the first appearance of Andalusiella in the upper part of the Early Campanian, and the first appearance of Senegalinium, in the lower part of the Late Campanian. During the Maastrichtian, provincialism continues characterizing N South America and Africa; the palynomorphs that have their last appearance are: Senegalinium bicavatum, Cerodinium granulostriatum, Andalusiella mauthei, Andalusiella gabonensis and Dinogymnium acuminatum.  The ratio of palynomorphs of marine origin POM (dinoflagellates, foraminiferal lining and acritarchs), to palynomorphs of continental origin POC (pollen, spores and fungis) reflects the changing position of the shoreline. The group of dinoflagellates is important in the mudstone units representing relatively high sea levels. The palynomorphs derived from fungis, pollen and spores, increase their contents in the sandy units representing relatively low sea levels. The almost total disappearance of dinoflagellates starts from the upper part of the Arenitas de San Luis de Gaceno Formation.